Isolation and diagnosis of Helicobacter pylori by a new method: Microcapillary culture - Allahverdiyev, Adil M.; Bagirova, Melahat; Caliskan, Reyhan; Tokman, Hrisi Bahar; Aliyeva, Hayat; Unal, Gokce; Oztel, Olga Nehir; Abamor, Emrah Sefik; Toptas, Hilal; Yuksel, Pelin; Kalayci, Fatma; Aslan, Mustafa; et al. (BAISHIDENG PUBLISHING GROUP INC, 2015)
AIM: To investigate the performance of the microcapillary culture method (MCM) in Helicobacter pylori (H. pylori) isolation and diagnosis. METHODS: Microcapillary culture (MC), classical culture (CC), rapid urease (CLO) test, and histopathologic examination (HE) were performed with biopsy samples. Homogenized biopsy samples were loaded into capillary tubes and incubated for 48 h at 37 degrees C without providing a microaerophilic environment. Additionally, three or four loops of the homogenized sample were inoculated in a ready-to-use selective medium (Becton Dickinson, Helicobacter Agar, Modified) specific for the isolation of H. pylori and incubated at 37 degrees C in a microaerophilic atmosphere provided by CampyGen (Becton Dickinson, GasPack). Bacteria reproducing in microcapillary tubes were evaluated in an inverted microscope and also were evaluated after performing a CC with the content. Results obtained by CC, CLO test, and HE were compared with those of MC. The diagnostic performances of the methods used in this study were evaluated for specificity, sensitivity, positive predictive value (PPV), negative predictive value (NPV), and CI. RESULTS: H. pylori was found positive by CLO test + HE and/or CC culture in 26 patient antrum and corpus biopsy samples. In 25 (25/26) patient biopsy samples, H. pylori was isolated by MCM, whereas in only 14 (14/26) patient biopsy samples, H. pylori was isolated by CC. CLO test and HE were found positive in 17 (17/26) patient biopsy samples. Comparing the results of the isolation of H. pylori by MCM, CC, CLO test, and HE, the sensitivity of the MCM was found as 96%, the specificity as 80%, the PPV as 83%, the NPV as 95%, and the 95% CI as 0.76 (chi(2) = 31.51, P < 0.01) whereas the sensitivity of the CC was found as 54% (chi(2) = 19.15, P < 0.01), and the sensitivity of the CLO test and HE were found as 65% (chi(2) = 25.26, P < 0.01). CONCLUSION: This new microcapillary cultivation method for H. pylori has high diagnostic sensitivity compared with CC, HE, and CLO tests.
Keywords: Microcapillary culture; Classical culture; New method; Isolation of Helicobacter pylori; Comparison; TURKISH PATIENTS; MAGNETOTACTIC BACTERIA; MICROCULTURE METHOD; CLINICAL-OUTCOMES; STOOL SPECIMENS; INFECTION; DYSPEPSIA; TESTS; LEISHMANIASIS; CHILDREN; Gastroenterology & Hepatology